The SAGE handbook of current developments in grounded theory - Bryant, Antony; Charmaz, Kathy (Thousand Oaks, California SAGE Publications Inc., 2019)
Building on the success of the bestselling The SAGE Handbook of Grounded Theory (2007), this title provides a much-needed and up-to-date overview, integrating revised and updated chapters with new ones, exploring recent developments in grounded theory and research methods in general. This is a method-defining resource for advanced students and researchers across the social sciences.
Includes bibliographical references and index (pages 662-679)
Keywords: Grounded theory